2006
DOI: 10.1111/j.1365-294x.2006.02991.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep genetic subdivision within a continuously distributed and highly vagile marine mammal, the Steller's sea lion (Eumetopias jubatus)

Abstract: The Steller's sea lion Eumetopias jubatus is an endangered marine mammal that has experienced dramatic population declines over much of its range during the past five decades. Studies using mitochondrial DNA (mtDNA) have shown that an apparently continuous population includes a strong division, yielding two discrete stocks, western and eastern. Based on a weaker split within the western stock, a third Asian stock has also been defined. While these findings indicate strong female philopatry, a recent study usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 44 publications
8
81
0
2
Order By: Relevance
“…Expected heterozygosity (ranging from 0.363 to 0.648) was similar or lower than reported at microsatellite loci for a number of other pinnipeds (Palo et al, 2001;Davis et al, 2002Davis et al, , 2008Hoffman et al, 2006;Coltman et al, 2007; ranging from 0.550 to 0.850 e.g., Hoelzel et al, 2001). Genetic diversity measures were significantly higher in South Australian colonies than in Western Australian colonies.…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 46%
See 1 more Smart Citation
“…Expected heterozygosity (ranging from 0.363 to 0.648) was similar or lower than reported at microsatellite loci for a number of other pinnipeds (Palo et al, 2001;Davis et al, 2002Davis et al, , 2008Hoffman et al, 2006;Coltman et al, 2007; ranging from 0.550 to 0.850 e.g., Hoelzel et al, 2001). Genetic diversity measures were significantly higher in South Australian colonies than in Western Australian colonies.…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 46%
“…Females are more likely to remain within their natal group and show sufficiently strong philopatry to create significant matrilineal substructure detectable with mitochondrial DNA (mtDNA) markers (Andersen et al, 1998;Burg et al, 1999;Hoelzel et al, 2001;Baker et al, 2005;Gonzalez-Suarez et al, 2009). However, when biparentally inherited nuclear markers have been used, while structuring may persist, overall the patterns are weaker, indicating that females are usually more philopatric than males (Andersen et al, 1998;Burg et al, 1999;Hoelzel et al, 2001;Hoffman et al, 2006;Gonzalez-Suarez et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of markers can underscore different population histories and difficult-to-study behaviors. As demonstrated by Hoffman et al (2006), even the same kind of marker can give rise to distinct results depending on the sample size and number of analyzed loci. By this way, conservation efforts and management recommendations need to be addressed with care and based on as much information as possible.…”
Section: Discussionmentioning
confidence: 99%
“…This has often been assumed within past studies that have modelled the extinction probability of the Steller sea lion in terms of eastern and western distinct population segments (e.g. Gerber and VanBlaricom, 2001;NMFS, 2008), even though genetic studies have tended to indicate that these sub-sections of the population are not freely mixing (Bickham et al, 1998;O'Corry-Crowe et al, 2006;Hoffman et al, 2006) and, as indicated by the present study, they may not be separate. Consequently, making the assumption that the eastern and western segments are freely mixing sub-populations is likely to result in an unrealistically inflated estimate of the extinction probability calling in to question the results of some past risk assessments of the Steller sea lion population.…”
Section: Scenarios For Future Trendsmentioning
confidence: 60%